Power system security assessment using artificial neural network / Mohd Fathi Zakaria - Zakaria, Mohd Fathi (2010)
The management of power system has become more difficult than earlier because power system are closer to security limits, fewer operators are engaged in the supervision and operation of power system. Power system security assessment has become a major concern today to avoid the instability in power system occur. One of the most significant considerations in applying neural networks to power system security assessment is the proper selection of training features. Modern inter connected power systems often consist of thousands of pieces of equipment each of which may have an effect on the security of the system. Neural networks have shown great promise for their ability to quickly and accurately predict the system security when trained with data collected from a load flow using Newton Raphson technique. A case study is performed on the IEEE 6-bus system to illustrate the effectiveness of the proposed techniques.